Economic approaches to organizations - Douma, S. W.; Schreuder, H. (Harlow, New York : Financial Times Prentice Hall, 2002)
Placing emphasis on the importance of economic issues and developments in the study of organizations and management, this book explains the behavioural theory of the firm, game theory, agency theory, transaction cost economics, economic contributions to strategic management, and evolutionary approaches.
Includes bibliographical references and index.
oif 13/03/15
Loan
Keywords: Managerial economics; Organizational theory; Microeconomics